Assessment of treatment outcomes for facial prostheses in patients with craniofacial defects: A pilot retrospective study - Brandão, Thais Bianca; Vechiato Filho, Aljomar José; de Souza Batista, Victor Eduardo [UNESP]; Prado Ribeiro, Ana Carolina; Filho, Hugo Nary; Chilvarquer, Israel; Nunn, Martha E.; Santos-Silva, Alan Roger; Barão, Valentim Adelino Ricardo; Wee, Alvin G. (Elsevier, 2017)
Statement of problem The longevity of silicone facial prostheses is short, and published data concerning this type of rehabilitation are limited. Purpose The purpose of this retrospective study was to identify predictive variables for prosthetic failure and to highlight the results that can be expected after treatment with silicone facial prostheses. Material and methods After institutional approval, patient records from a single Brazilian institution for the time period 2004 to 2015 were assessed. A standardized form was used to collect patient data. Frailty survival modeling (simple random effects survival model) was used to test whether age, sex, type of prosthesis, source of defect, number of implants, and type of retention have a direct impact on the prosthetic failure rate (α=.05). Results Auricular prostheses were the most frequently fabricated prostheses. Eighty-four prostheses were fabricated during the follow-up period. The overall survival rate for facial prostheses was 34.5%. Color alteration was the most common reason for new prostheses (27.38%). The implant success rate was 98.18%. The number of implants approached statistical significance (P=.06) with a reduced risk of failure when the patient had 2 implants compared with patients with zero implants and patients with more than 2 implants. Conclusions Patients should be recalled frequently so that retouches can be performed, avoiding the repeated fabrication of new prostheses. Well-designed studies are necessary to identify more relevant complications and factors that lead to prosthetic failure.